Advances in taxation. Vol. 14 - Porcano, Thomas M. (Emerald, 2002)
This title is part of a series dealing with all aspects of taxation, including tax policy and issues at the federal, state, local, or international level. The series primarily publishes empirical studies that address compliance, computer usage, education, legal, planning, or policy issues.
Keywords: Taxation.; Taxation -- United States.; elektronické knihy; electronic books